Leucas deodtkarii Billore et Hemadri-a New Species of Lamiaceae from the Sahyadri Range, Maharashtra State - Billore, K. V.; Hemadri, Koppula (Indian Forester, 1970)
Leucas deodikarii Biltore et Hemadri, sp. nov. collected from the Sahyadri range of Maharashtra State, is described and illustrated.